The Effect of Using PQ4R Strategy on The Ability of The Second Year Students of Mts Darul Hikmah Pekanbaru in Comprehending Recount Texts - Nina Fitriani; Supriusman Supriusman; Maria Safriyanti (Madah: Jurnal Bahasa dan Sastra, 2021)
Abstract This research aimed to find out if there is a significant effect of using PQ4R strategy on the ability of the second year students of MTs Darul Hikmah Pekanbaru in comprehending recount texts. This is a pre-experimental research with one group pretest and posttest design. This research used quantitative data and the instrument used to collect the data was a reading test in multiple choice forms. As the result, the mean score of pre-test is 59.03 and post-test is 62.97. In the other words, the mean score of post-test is higher than the mean score of pre-test. The result also showed that the value of t-test (8.907) is higher than t-table (3.365) at the significance level 0.1%. It means that Alternative Hypothesis (Ha) is accepted. It can be concluded that there is a significant effect of using PQ4R strategy on the ability of the second year students of MTs Darul Hikmah Pekanbaru in comprehending recount texts. It is suggested that in understanding recount text is one of alternatives, the teacher needs to focus on the students’ understanding of the sentences on the texts. Abstrak Penelitian ini bertujuan untuk mengetahui apakah ada pengaruh signifikan penggunakan strategi PQ4R pada kemampuan siswa tahun kedua MTs Darul Hikmah Pekanbaru dalam memahami teks recount. Penelitian ini adalah penelitian pra-eksperimental dengan desain satu kelompok pretest dan posttest. Penelitian ini menggunakan data kuantitatif dan instrumen yang digunakan untuk mengumpulkan data adalah tes membaca dalam bentuk pilihan ganda. Hasilnya, nilai rata-rata pre-test adalah 59,03 dan post-test adalah 62,97. Dengan kata lain, skor rata-rata post-test lebih tinggi daripada skor rata-rata pre-test. Hasil penelitian juga menunjukkan bahwa nilai t-test (8,907) lebih tinggi dari t-tabel (3,365) pada tingkat signifikansi 0,1%. Ini berarti bahwa Hipotesis Alternatif (Ha) diterima. Dapat disimpulkan bahwa ada pengaruh yang signifikan menggunakan strategi PQ4R pada kemampuan siswa tahun kedua MTs Darul Hikmah Pekanbaru dalam memahami teks recount. Disarankan bahwa dalam memahami teks recount, salah satu alternatif adalah guru perlu fokus pada pemahaman siswa tentang kalimat pada teks.